Evaluation of CeaseFire, a Chicago-based Violence Prevention Program, 1991-2007 - Skogan, Wesley G. ([Verlag nicht ermittelbar], 2015)
This study evaluated CeaseFire, a program of the Chicago Project for Violence Prevention. The evaluation had both outcome and process components. The outcome evaluation assessed the program's impact on shootings and killings in selected CeaseFire sites. Two types of crime data were compiled by the research team: Time Series Data (Dataset 1) and Shooting Incident Data (Dataset 2). Dataset 1 is comprised of aggregate month/year data on all shooting, gun murder, and persons shot incidents reported to Chicago police for CeaseFire's target beats and matched sets of comparison beats between January 1991 and December 2006, resulting in 1,332 observations. Dataset 2 consists of data on 4,828 shootings that were reported in CeaseFire's targeted police beats and in a matched set of comparison beats for two-year periods before and after the implementation of the program (February 1998 to April 2006). The process evaluation involved assessing the program's operations and effectiveness. Researchers surveyed three groups of CeaseFire program stakeholders: employees, representatives of collaborating organizations, and clients. The three sets of employee survey data examine such topics as their level of involvement with clients and CeaseFire activities, their assessments of their clients' problems, and their satisfaction with training and management practices. A total of 154 employees were surveyed: 23 outreach supervisors (Dataset 3), 78 outreach workers (Dataset 4), and 53 violence interrupters (Dataset 5). The six sets of collaborating organization representatives data examine such topics as their level of familiarity and contact with the CeaseFire program, their opinions of CeaseFire clients, and their assessments of the costs and benefits of being involved with CeaseFire. A total of 230 representatives were surveyed: 20 business representatives (Dataset 6), 45 clergy representatives (Dataset 7), 26 community representatives (Dataset 8), 35 police representatives (Dataset 9), 36 school representatives (Dataset 10), and 68 service organization representatives (Dataset 11). The Client Survey Data (Dataset 12) examine such topics as clients' involvement in the CeaseFire program, their satisfaction with aspects of life, and their opinions regarding the role of guns in neighborhood life. A total of 297 clients were interviewed.